Towards the solution of an integrable spin chain - Nepomechie, Rafael I.; Pimenta, Rodrigo A.; Retore, Ana L. [UNESP] (IOP Publishing, 2019)
Two branches of integrable open quantum-group invariant Dn+1 (2) quantum spin chains are known. For one branch (ϵ = 0), a complete Bethe ansatz solution has been proposed. However, the other branch (ϵ = 1) has so far resisted solution. In an effort to address this problem, we consider here the simplest case n = 1. We propose a Bethe ansatz solution, which however is not complete, as it describes only the transfer-matrix eigenvalues with odd degeneracy. We also consider a proposal for the missing eigenvalues.
Keywords: Bethe ansatz; integrable quantum spin chains; quantum group